APPLICATIONS FOR TURBO PASCAL VERSION SEVEN PRACTICUM ASSESSMENT SYSTEM IN SMP NEGERI 89 JAKARTA - Nugroho Budi Santoso; Ir. Aqwam Rosadi.K,MM Ir. Aqwam Rosadi.K,MM (Jurnal Sistem Informasi, 2001)
Writing is about the problems that arise in the assessment system. The authorproposes an application to solve problems in the assessment system.This application can store and process the student ujain value number value into theletter. Attached to the end writing programs to support the application.